Adolescents' physical activity trends over the years: a three-cohort study based on the Health Behaviour in School-aged Children (HBSC) Portuguese survey. Issue 10 (6th October 2014) - Marques, Adilson; Gaspar de Matos, Margarida
Abstract : Objective: Many young people do not practise enough physical activity (PA) to benefit their health. The three-cohort study aimed to investigate the prevalence of PA and understand the trends between 2002 and 2010, using a representative sample of Portuguese adolescents. Design, setting and participants: The participants were 8483 adolescents (4067 boys, 4416 girls) who participated in the Health Behaviour in School-aged Children Portuguese survey in 2002, 2006 and 2010. Design, setting and participants: A questionnaire was used to collect data of PA. Analyses were run separately for boys and girls. Results: Boys aged 15–17 reported practising 3.5±1.9 times a week in 2002, 3.9±1.9 times a week in 2006 and 3.8±1.9 times a week in 2010, with a significant increase from 2002 to 2006/2010 (p<0.05). PA practice during the past 7 days decreased from 4.2±2.1 to 3.9+1.9 between 2002 and 2006 (p<0.001) and also decreased from 4.4±2.1 to 3.8±1.9 between 2006 and 2010 (p<0.001). Among girls, PA practices during the past 7 days declined significantly from 3.5±1.9 to 2.7±1.7 between 2002 and 2006 (p<0.001), and from 3.3±1.9 to 2.9±1.7 between 2006 and 2010 (p<0.001). Conclusions: The study points to age as a factor related to diminished PA participation. The study also revealed that the prevalence of PA has decreased over the years for the same age groups.